HUBUNGAN HASIL BELAJAR DASAR DESAIN DAN KREATIVITAS TERHADAP HASIL BELAJAR PEMBUATAN HIASAN - Rustanto (LPPM, Universitas Negeri Jakarta, 2021)
This study aims to determine the relationship between basic lessons of fashion design and creativity to student learning outcomes in the subject of making decoration. The test site of this research is conducted at SMK Negeri in DKI Jakarta study program of expertise of fashion field of tourism expertise. This research is done by giving test in the form of theory test and practice on Making Ornament subject. The method used in this research is quantitative research method correlational relationship between variables by using questionnaire. Using a sample of 172 students. The data generated by each variable is tested by using the validity, reliability, normality, regression, and correlation test. Test results in this study are as follows: a) There is a positive relationship between the basic subjects of design with the results of learning decoration, b) There is a positive relationship between creativity with the results of decorative learning and c) There is a positive relationship between basic subjects Design and creativity together towards the learning outcome of decoration making Keywords: competency for design basic, creativity, the result of embroidery.